Navigating dual risks: Ovarian cancer prevention and cardiovascular health in patients with hereditary cancer syndromes - Keenahan, Laura; Ahsan, Muhammad Danyal; Mecklai, Alicia; Frey, Melissa K. (Gynecologic oncology reports, 2025)
•Surgical removal of ovaries and fallopian tubes is recommended for many hereditary cancer syndrome carriers before menopause.•Premature surgical menopause is associated with an increased risk of cardiovascular disease.•Clinicians caring for patients with premature surgical menopause should consider cardiovascular health implications.